Design and Analysis of the Independent Communication Module for LESPA- Lunar Electric Surface Potential Analyzer - Prakash, Arunima; R. Marur, Diwakar; Namdeo, Sakshi (International Journal of Engineering and Technology, 2018)
Moon, our closest celestial neighbor and Earthâ€™s only natural satellite is of utmost scientific importance. So far there have been 67 missions to the Moon, thus to enhance and aid further research understanding of lunar surface is vital. The Moon meets the Earthâ€™s magnetotail (an extension of Earthâ€™s magnetosphere) twice in a month encountering a gigantic sheet of ionized particles or plasma. These charged particles intersperse on the lunar dust and give it a negative charge. The electric field created by this phenomenon creates a substantial potential difference across the two sides of the lunar surface. Electrified dust grains can adhere to machinery and the large electric fields can affect electronics of landers or payload machinery. A payload is proposed Lunar Electric Surface Potential Analyzer (LESPA) to measure the effects of these magnetotail crossings. LESPA will need to establish a low BER link with the in-orbit lunar satellite at optimum frequencies to relay the raw data. This paper aims to analyze and study the link budget requirements for designing an Independent Communication Module (ICM) for LESPA as well as antenna models for the transmitter. The scope of the designed ICM is to ultimately assist in designing lander missions for future lunar exploration and aid in future lunar exploration missions and colonization activities.Â